PENGARUH TERPAAN INFORMASI DAN LITERASI MEDIA TENTANG HOAKS VAKSIN COVID-19 TERHADAP KECEMASAN MASYARAKAT : Survei Pada Generasi X Di Wilayah Jakarta - Mochammad Sulthan Nadief, (2022)
In 2019, a new virus outbreak emerged called Corona and over time it became a pandemic. With social media became closer to public during the pandemic, information is getting easier to obtain. However, not all information spread across various social media, especially WhatsApp, is true. This study describes the relationship between the effect of information exposure and media literacy of COVID-19 vaccination hoaxes to public anxiety, particularly the X Generation community in Jakarta. The theory used in this study is the Individual Differences Theory, with the assumption of this theory explains that the effect of mass media exposure has different effects between individual based on each individual's background. The research method used in this research is Quantitative with survey method, by distributing questionnaries to 100 respondents of RW02 Tanjung Duren Selatan, West Jakarta, aged 42 to 57 years. The results of this study showed that there was a simultaneous effect of 6,5% on information exposure and media literacy of COVID-19 vaccine hoaxes on public anxiety. The hypothesis test shows that H01 accepted, H1 rejected and H02 rejected, H2 accepted. It can be concluded that there is an effects of media literacy of COVID-19 vaccine hoaxes on public anxiety of X Generation in RW02 Tanjung Duren Selatan, Jakarta.